Econometric Business Cycle Research - Tinbergen, J. (Review of Economic Studies, 1940)
Econometric Business Cycle Research J. Tinbergen J. Tinbergen The Hague, Holland Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 7, Issue 2, February 1940, Pages 73–90, https://doi.org/10.2307/2967472 Published: 01 February 1940